Preparation and isolation of isobenzofuran - Peters, Morten K.; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2017)
The synthesis, isolation and characterization of isobenzofuran are described in this publication. Isobenzofuran is of general interest in synthetic and physical organic chemistry because it is one of the most reactive dienes known. A number of synthetic pathways have been published which all suffer from disadvantages such as low yields and difficult purification. We present a synthetic pathway to prepare isobenzofuran in laboratory scale with high yields, from affordable, commercially available starting materials.
Keywords: [4 + 2] cycloaddition; Diels–Alder; isobenzofuran; trapping reagent